2018
DOI: 10.3390/su10093044
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Destination Social Responsibility on Tourists’ Satisfaction: The Mediating Role of Emotions

Abstract: The purpose of this study is to define destination social responsibility as a multidimensional construct and examine the relationships between destination social responsibility, tourists’ emotions and their satisfaction, through the lens of corporate social responsibility. A model is empirically tested with a sample of 359 random foreign tourists visiting Hoi An, Vietnam. The results indicate that all destination social responsibility dimensions, including economic, environmental, legal–ethical, and philanthro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 55 publications
(92 reference statements)
0
31
0
1
Order By: Relevance
“…DSR emphasizes the importance of responsible efforts of all involved stakeholders to build tourist destinations in a sustainable manner. In light of the definition of DSR, it is obvious that DSR should be jointly supported by not only the public and the private sectors involved in a destination, but also the tourists [10,11]. If DSR is not preferred by tourists, it will weaken the motive of DSR, and destination sustainability will be difficult to achieve.…”
Section: Dsr For Sustainable Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…DSR emphasizes the importance of responsible efforts of all involved stakeholders to build tourist destinations in a sustainable manner. In light of the definition of DSR, it is obvious that DSR should be jointly supported by not only the public and the private sectors involved in a destination, but also the tourists [10,11]. If DSR is not preferred by tourists, it will weaken the motive of DSR, and destination sustainability will be difficult to achieve.…”
Section: Dsr For Sustainable Developmentmentioning
confidence: 99%
“…Su et al [12] investigated the impact of DSR perception on the intention of tourists to revisit a destination and recommend the place to their acquaintances and found that DSR is positively associated with both revisit and referral intentions. According to the study by Tran et al [11], DSR has shown a positive effect on tourists' satisfaction through a mediating effect on their emotions.…”
Section: Dsr For Sustainable Developmentmentioning
confidence: 99%
See 3 more Smart Citations